3485 Frailty Associated with Increased Rates of Acute Cellular Rejection Within 3 Months After Liver Transplantation. (27th March 2019) - Fozouni, Laila; Lebsack, Adrienne; Mohamad, Yara; Freise, Chris; Stock, Peter; Lai, Jennifer
Abstract : OBJECTIVES/SPECIFIC AIMS: There is currently a gap in the literature regarding the relationship between acute cellular rejection and frailty in LT patients. We aimed to evaluate the association between frailty and acute cellular rejection in LT patients. METHODS/STUDY POPULATION: Included were LT recipients from 2014-16 at a single center who had a frailty assessment prior to LT using the Liver Frailty index consisting of grip strength, chair stands, and balance. Frailty was defined by a Liver Frailty Index > 4.5. Data on acute cellular rejection at 3 months (primary outcome) and immunosuppression regimens were collected from medical chart review. Univariable and multivariable logistic regression assessed the associations between frailty and acute cellular rejection. RESULTS/ANTICIPATED RESULTS: A total of 241 LT recipients were included. Of these, 37% were female, 55% had Hepatitis C, and the median (IQR) age was 60 (54-65); 46 (19%) were classified as frail. 98% of patients were on a combination of mycophenolate, corticosteroids and tacrolimus on discharge compared to 80% by 3 months. Within the first 3 months post-LT, 7 (15%) of frail patients versus 10 (5%) (p = 0.02) of non-frail patients experienced acute cellular rejection. In univariable logistic regression, frailty was associated with a 3.3 times higher odds of acute cellular rejection at 3 months (95%CI 1.19, 9.26, p = 0.02); age (OR 0.91), Black race (OR 3.2), autoimmune disease (OR 2.3), and diabetes (OR 0.3) were also associated with acute cellular rejection at 3 months with a p-value<0.20. In a multivariate analysis, after adjusting for age, frailty remained significantly associated with rejection (OR 3.06, 95%CI 1.04, 9.01, p = 0.043). There were no significant differences in immunosuppression regimens or rates of mycophenolate dose reduction in the first 3 months between frail and non-frail patients. DISCUSSION/SIGNIFICANCE OF IMPACT: Frailty is associated with an increased rate of acute cellular rejection within 3 months post-LT, despite similar immunosuppression regimens and doses. Future studies should evaluate whether frailty should be considered in the management of immunosuppression in the early post-transplant period.